Bioethanol Production From H2/CO2 by Solventogenesis Using Anaerobic Granular Sludge: Effect of Process Parameters - He, Yaxue; Cassarini, Chiara; Lens, Piet N. L. (Frontiers in Microbiology, 2021)
CO2 fermentation by biocatalysis is a promising route for the sustainable production of valuable chemicals and fuels, such as acetic acid and ethanol. Considering the important role of environmental parameters on fermentation processes, granular sludge from an industrial anaerobic wastewater treatment system was tested as inoculum for ethanol production from H2/CO2 at psychrophilic (18°C), submesophilic (25°C) and mesophilic (30°C) temperatures. The highest acetic acid and ethanol production was obtained at 25°C with a final concentration of 29.7 and 8.8 mM, respectively. The presence of bicarbonate enhanced acetic acid production 3.0 ~ 4.1-fold, while inhibiting ethanol production. The addition of 0.3 g/L glucose induced butyric acid production (3.7 mM), while 5.7 mM ethanol was produced at the end of the incubation at pH 4 with glucose. The addition of 10 μM W enhanced ethanol production up to 3.8 and 7.0-fold compared to, respectively, 2 μM W addition and the control. The addition of 2 μM Mo enhanced ethanol production up to 8.1-fold and 5.4-fold compared to, respectively, 10 μM Mo and the control. This study showed that ethanol production from H2/CO2 conversion using granular sludge as the inoculum can be optimized by selecting the operational temperature and by trace metal addition.